(+)4-Cholesten-3-one promotes differentiation of neural stem cells into dopaminergic neurons through TET1 and FoxA2. (14th September 2020) - Ye, Sen; Zhong, Jun; Huang, Jiapei; Zhang, SaiXia; Li, Hui; Chen, DongFeng; Li, CaiXia
Highlights: (+)4-cholesten-3-one increase the tyrosine hydroxylase(TH). (+)4-cholesten-3-one increase the global DNA demethylation and the transcription factor fork-head box a2 (FoxA2). (+)4-cholesten-3-one increase the binding of TET1 and FoxA2. Binding of TET1 and FoxA2 is essential for NSC differentiation to dopaminergic neurons. (+)4-cholesten-3-one can induce NSC differentiation into dopaminergic neurons though TET1 and FoxA2. Abstract: In this paper, we report the results of treating cells with an effective small molecule, (+)4-cholesten-3-one (PubChem CID: 91477), which can promote neural stem cell(NSC) differentiation into dopaminergic neurons. This study used rat neural stem cells stimulated with two different concentrations (7.8 μM and 78 μM) of (+)4-cholesten-3-one. Cell phenotypic analysis showed that (+)4-cholesten-3-one induced NSC differentiation into dopaminergic neurons, and the level of tyrosine hydroxylase(TH), which is specific for dopaminergic cells, was significantly increased compared with that of the drug-free control group. Furthermore, in this study, we found that this effect may be related to the transcription factor fork-head box a2 (FoxA2) and ten-eleven translocation 1 (TET1). The expression of TET1 and FoxA2 was upregulated after treatment with (+)4-cholesten-3-one. To verify the relationship between (+)4-cholesten-3-one and these genes, we found that the binding rate of TET1 and FoxA2 increased after the application of (+)4-cholesten-3-one, as confirmed by a coimmunoprecipitation (Co-IP) assay. With a small interfering RNA (siRNA) experiment, we found that only when Tet1 and Foxa2 were not silenced was the mRNA level of Th increased after (+)4-cholesten-3-one treatment. Taken together, these data show that (+)4-cholesten-3-one can promote the differentiation of NSCs into dopaminergic neurons by upregulating the expression of TET1 and FoxA2 and by increasing their binding. Thus, (+)4-cholesten-3-one may help address the application of neural stem cell replacement therapy in neurodegenerative diseases.